Taxonomic and nomenclatural acts formalizing the classification provided in the world catalogue of the Cleonini (Curculionidae: Lixinae) - Meregalli, Massimo (Zootaxa, 2017)
Several taxonomic and nomenclatural acts required to formalize the classification provided in the online World Catalogue of the Cleonini are proposed. The genera Epirrhynchus Schoenherr, 1826 and Nomimonyx Faust,1904 are excluded from the Lixinae: Cleonini and provisionally referred to the Cyclominae. Phaulosomus kilimanus Faust, 1904 is designated as type species of genus Phaulosomus Faust, 1904. The lectotype of Curculio nebulosus Linnaeus, 1758 is designated. New synonymies are proposed for 20 species, new combinations are proposed for 13 species, 11 species are resurrected from synonymy, 1 subspecies is resurrected from synonymy, 1 species is promoted to species rank from subspecies.